Whole world vegetarian - Simmons, Marie (Houghton Mifflin Harcourt, 2016)
"Big-flavored vegetarian dishes from around the globe, from the James Beard Award- and IACP Award-winning author Marie Simmons The best of our vegetarian recipes have always drawn inspiration from other cultures. In Whole World Vegetarian, Marie Simmons follows her culinary wanderlust, bringing together a collection of bold, imaginative dishes and seamlessly adapting them to contemporary tables. Cooks can expect a wealth of sumptuous options: rice- and corn-stuffed poblano chiles; Greek-style mac-and-cheese with summer squash; Indonesian vegetable salad with peanut dressing. Even the homiest dishes deliver rich rewards, like South American pumpkin-black bean stew with prunes. All have fresh twists: In a zucchini lasagna, squash replaces pasta, and a cold beet soup is replete with chopped fresh tomatoes, cucumbers, and apples. A Persian herb omelet gets an unexpected lift with baking powder. From a quick and little-known dip of Iranian yogurt, spinach, and caramelized onions garnished with toasted walnuts to shakshuka, a spicy Tunisian ratatouille crowned with poached eggs and fresh herbs, all become accessible and inviting under Simmons' guidance."--